2010
DOI: 10.1016/s1474-4422(10)70168-x
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography in multiple sclerosis: a systematic review and meta-analysis

Abstract: Optical coherence tomography (OCT) is a new method that could aid analysis of neurodegeneration in multiple sclerosis (MS) by capturing thinning of the retinal nerve fibre layer (RNFL). Meta-analyses of data for time domain OCT show RNFL thinning of 20.38 microm (95% CI 17.91-22.86, n=2063, p<0.0001) after optic neuritis in MS, and of 7.08 microm (5.52-8.65, n=3154, p<0.0001) in MS without optic neuritis. The estimated RNFL thinning in patients with MS is greater than the extent expected in normal ageing, prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
470
3
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 543 publications
(537 citation statements)
references
References 103 publications
(94 reference statements)
32
470
3
14
Order By: Relevance
“…Unfortunately, the sample size was too small to investigate the impact of ON in depth. ON leads to a predominant loss of RNFL thickness in the anterior visual pathway, which translates only to a much lower extend of volume loss in related brain regions (Balcer et al., 2015; Petzold et al., 2010). However, accounting for previous ON in our models was sufficient to preserve the strong association with the insula in the whole cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the sample size was too small to investigate the impact of ON in depth. ON leads to a predominant loss of RNFL thickness in the anterior visual pathway, which translates only to a much lower extend of volume loss in related brain regions (Balcer et al., 2015; Petzold et al., 2010). However, accounting for previous ON in our models was sufficient to preserve the strong association with the insula in the whole cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal nerve fiber layer (RNFL) thickness has already been used as an OCT endpoint in a multicenter phase 2 trial and will probably be increasingly used due to the easy, fast, and noninvasive assessment (Sühs et al., 2012). Moreover, OCT measures seem to have moderate but consistent correlation with brain parenchymal fraction and brain volume (Balcer et al., 2015; Petzold et al., 2010). The correlation with gray and white matter volume is inconsistent and correlations are generally weak to moderate (Young et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…1 Recent advances in ultra-high resolution spectral domain OCT make this imaging modality more useful in research and patient care. 2 OCT can provide high-resolution cross-sectional images of the retina to aid in identifying, monitoring, and quantitatively assessing ocular diseases 1,3,4 and ocular manifestations of diseases in the central nervous system disorders, such as multiple sclerosis 5,6 and stroke. Most of commercially available OCT devices have an approximately axial resolution of 5 μm and are limited to a few segmented intraretinal layers, although the segmentation is mostly automatic.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the recent few years, several studies demonstrated the presence of axonal degeneration even in the initial stages of MS. [1][2][3][4] Axonal loss is an irreversible process and is related to permanent disability observed in MS; therefore, the monitoring of axonal loss is important for the follow-up of the disease and the development of a targeted treatment strategy. 2 Retinal cell axons are part of the CNS, and do not have a myelin sheath until they penetrate the lamina cribrosa, thus the investigation of retina might be ideal for visualising the processes of neuroaxonal degeneration and understanding mechanisms of brain tissue damage in multiple sclerosis. 5 One of the relatively novel techniques for investigation of retina is optical coherence tomography (OCT).…”
Section: Introductionmentioning
confidence: 99%